Assessment of the applicability of cast steels for manufacturing shaft crusher components - Fyk, Sviatoslav (Видавництво Львівської політехніки, 2024)
The production of shredding shafts for industrial shredders presents significant challenges due to the high mechanical loads and exposure to abrasive materials these components must endure. Traditional designs involve the complex and labour-intensive process of welding sprockets to the main shaft, which increases manufacturing, labour, and maintenance costs. This study explores a novel approach to manufacturing shredding shafts by implementing cast sprockets, significantly reducing the complexity and expense associated with traditional designs. The proposed design aims to decrease material and maintenance costs by simplifying the assembly process and optimising material selection, thereby enhancing overall efficiency. This study evaluates steels obtained by casting into sand-clay moulds. The research includes a detailed analysis of sample materials’ elemental composition, hardness, tensile strength, and impact toughness. The results indicate that while alternative cast steels (Sample 1 and Sample 2) offer costsaving potential, they exhibit increased hardness and brittleness, particularly evident in impact bending tests compared to Hardox 450 steel. Sample 1 and Sample 2, for instance, demonstrated a significant reduction in impact toughness and higher susceptibility to cracking post-welding, attributed to higher carbon equivalent values. Although these alternative materials present economic advantages regarding production costs, their decreased plasticity and increased crack susceptibility suggest limitations for use in high-impact environments typical of industrial shredding equipment. In conclusion, the findings provide valuable insights into the trade-offs in selecting alternative materials for shredding shaft components. While cast steels may reduce costs and simplify production, further optimization of material properties is required to ensure that these alternatives meet the rigorous demands of industrial applications. These results contribute to developing more efficient, cost-effective designs for shredding equipment components.
Keywords: shredding machines; hardness; strength; impact toughness; welding; carbon equivalent